HINDUISASI DI KAWASAN MEGALITIK GUNUNG SLAMET - Sulistyarto, Priyatno Hadi (Berkala Arkeologi, 2003)
The life of the megalithic community carries out the tradition continuously until the influence of Hindu-Buddhist culture. Hinduization in this area was carried out by utilizing megalithic worship facilities, including mortar and phallus stones. The concept of worship that is used is still the same, namely fertility, a concept that is absolutely necessary in an agricultural society. The process of Hinduization can be seen in the use of stone mortar and phallus together, namely by erecting the phallus or menhirs into the mortar holes so that they resemble a lingga-yoni arrangement. Thus the phallus or menhir function represents the existence of the lingga, while the mortar function represents the presence of yoni. Lingga and yoni are objects as symbols in Hinduism.